Asymmetric Organocatalytic Homologation: Access to Diverse Chiral Trifluoromethyl Organoboron Species. Issue 58 (18th August 2022) - Jayarajan, Ramasamy; Kireilis, Tautvydas; Eriksson, Lars; Szabó, Kálmán J.
Abstract: A broad range of aliphatic, aromatic, and heterocyclic boronic acids were successfully homologated using trifluorodiazoethane in the presence of BINOL derivatives to provide the corresponding chiral trifluoromethyl containing boronic acid derivatives in high yields and excellent enantioselectivity. The in situ conversion of the chiral transient boronic acids to the corresponding alcohols or β ‐CF3 carboxylates are also demonstrated. Abstract : Highly enantioselective α‐trifluoromethylated aliphatic, aromatic, and heterocyclic boronic acids and boronates were synthesized from simple feedstocks.